2013
DOI: 10.1080/14330237.2013.10820614
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence as a Predictor of Postgraduate Students' Psychosocial Employability Attributes

Abstract: This study determined the influence of individuals' emotional intelligence on their psychosocial employability attributes. A cross-sectional quantitative survey was conducted. A non-probability sample of 304 employed postgraduate students (predominantly early career black = 70 %; females = 64 % with a mean age of 26 -40 years) participated in the study. Multiple regressions were used to analyse the data. Emotional intelligence was found to be a significant predictor of the participants' psychosocial employabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Women also score higher than men on emotional intelligence, a dimension that predicts employability. 28 In conclusion, this study manipulated the type of language used on Facebook profiles and found that while no effect was shown on measures of social, physical, or task attractiveness, owners of profiles containing correct language were rated as more employable than owners of those containing incorrect language or text speak. Results highlight the dichotomy between the primary social function of social networks and the consequences of presenting information online.…”
Section: Discussionmentioning
confidence: 76%
“…Women also score higher than men on emotional intelligence, a dimension that predicts employability. 28 In conclusion, this study manipulated the type of language used on Facebook profiles and found that while no effect was shown on measures of social, physical, or task attractiveness, owners of profiles containing correct language were rated as more employable than owners of those containing incorrect language or text speak. Results highlight the dichotomy between the primary social function of social networks and the consequences of presenting information online.…”
Section: Discussionmentioning
confidence: 76%
“…In summary, most of the previous academic efforts have been made in detecting the components of undergraduates’ employability ( McQuaid and Lindsay, 2005 ; Fugate and Kinicki, 2008 ; Clarke, 2018 ; Zhang et al, 2022 ) and exploring the influencing factors such as career adaptability ( Udayar et al, 2018 ; Atitsogbe et al, 2019 ), self-efficacy ( Berntson et al, 2008 ; Dacre Pool and Qualter, 2013 ), soft skills ( Finch et al, 2013 ), emotional intelligence ( Potgieter and Coetzee, 2013 ), career satisfaction ( Nauta et al, 2009 ; Dacre Pool and Qualter, 2013 ), academic performance ( Pinto and Ramalheira, 2017 ), and work-integrated learning ( Jackson, 2015 ), but little research has been done pertaining to how and to which extent the innovation capability and social adaptability of undergraduates affect their employability. In the meanwhile, no previous research has simultaneously taken innovation capability, social adaptability, self-efficacy, and undergraduates’ employability into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Women typically score higher than men on emotional intelligence. As this dimension is a predictor of employability (Potgieter and Coetzee, 2013) it could explain these results. Previous studies (e.g., Scott et al, 2014) found higher employability ratings for female than male targets using samples where the majority of participants were also women.…”
Section: Discussionmentioning
confidence: 87%